Functional Evaluation of Asibot: A New Approach on Portable Robotic System for Disabled People - Alberto Jardón; Concepción A. Monje; Carlos Balaguer (Applied Bionics and Biomechanics)
In this work, an innovative robotic solution for human care and assistance is presented. Our main objective is to develop a new concept of portable robot able to support the elderly and those people with different levels of disability during the execution of daily tasks, such as washing their face or hands, brushing their teeth, combing their hair, eating, drinking, and bringing objects closer, among others. Our prototype, ASIBOT, is a five degrees of freedom (DOF) self-contained manipulator that includes the control system and electronic equipment on board. The main advantages of the robot are its light weight, about 11 kg for a 1.3 m reach, its autonomy, and its ability to move between different points (docking stations) of the room or from the environment to a wheelchair and vice versa, which facilitates its supportive functions. The functional evaluation of ASIBOT is addressed in this paper. For this purpose the robotic arm is tested in different experiments with disabled people, gathering and discussing the results according to a methodology that allows us to assess users' satisfaction.